Arabic Practice in the Language Environment l Mumarasah al-Lughah al-‘Arabiyah fi Bi’ah Lughawiyyah - Kasmantoni, Kasmantoni; Aflisia, Noza; ‘Atiyah, Isma Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2022)
The concept of learning speaking skills was urgently discussed to become a cornerstone in practice. Many students do not understand correctly the concept of speaking Arabic which is the characteristic of someone who is proficient in Arabic. The purpose of this study was to analyze the idea of Mohammed Mohammed Imam Daoud in learning speaking skills in Arabic Language. A qualitative descriptive method was used as the research design. Data analysis techniques included formulating research problems, conducting literature studies, determining units of observation and units of analysis, creating categorization and coding guidelines, coding data, and processing data. The results of the research that the ability to be tired of the meanings of the soul in different approvals and the ability to use vocabulary in the social context. The method of speaking skill was according to Muhammad Daoud's approach to listening skill and speaking skill. Adab of learning the speaking skills are fidelity, seriousness in training, and continuous, so the learners would be skillful. The information would make knowledge but training and practice would create skill cooperation with the teacher and colleagues and humility in their lives. The key of success in speaking can also be done with the application of Arabic in the language environment. Muhammad Imam Dawood's idea of teaching speaking skills was important for developing the quality of learning speaking skills at the primary, intermediate and advanced levels. The application of Arabic in practice would increase the fluently in speaking performance.